A Survey of the quality of nursing care in several health districts in South Africa. - Naidoo Joanne R; Uys Leana R (BMC, 2004)
Abstract Background South Africa is currently focusing strongly on human resource development. The purpose of this study was to describe and compare the quality of nursing service and care in three health districts in the KwaZulu Natal Province. To identify deficiencies which could be addressed by education and training, it might be useful to measure the quality of care given by nurses. Methods From March to August 2002 a survey was done in six hospitals and six clinics in three health districts of the KwaZulu-Natal province of South Africa. Five different aspects of care was evaluated; hand-over from one nursing shift to another, implementation of universal precautions, patient satisfaction, nursing records, management of chronic illnesses. All these aspects were evaluated using checklists based on record reviews or direct observation, except for patient satisfaction, which was evaluated by questionnaires. Results The average scores on the different aspects varied from 11% (for nursing records) to 73% (for management of chronic diseases). Specific problems became evident. In one district three out of four hand-overs between shifts of nurses scored less than 50%. In all three districts the use of protective gear scored low (43%). While the average score for management of chronic illnesses were high at 73%, the blood pressures of only 23% was within the target range, and the blood sugar of only 38% of patients were controlled. Patient satisfaction averaged 72% across the three districts. Conclusion The quality of care measurements identified specific training needs, but other management strategies are probably also indicated.